Ensaios sobre política monetária - Mendonça, Diogo de Prince (2015)
This thesis includes three essays about monetary policy. The first essay covers the channel that financial crises increase the allocative inefficiency in emerging countries. The second essay addresses the degree of non-neutrality of money in Brazil according to the Golosov an Lucas (2007) model. The third essay covers the estimation of the hazard function slope in pricing to Brazil by methodology of Finite Mixture Model.